Konsep Keseimbangan Harta dalam Al-Qur’an: Analisis Ayat-Ayat Al Qur’an mengenai Hak Milik dan Distribusi Harta Kekayaan - Dwi Harjana; Achmad Abubakar; Muhammad Galib (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
One of the important themes of property rights in which the Qur'an provides the position of property rights, both how to obtain property rights, maintain property rights and distribute wealth that has been syarized. This paper aims to reveal the role of the Qur'an in maintaining property rights and distributing property so as to create a balance of property. The method used in the research is descriptive qualitative and tafsir approach from the language of the verse in the Qur'an relating to maintaining property rights and distributing wealth. This study confirms that the Qur'an teaches Muslims to acquire wealth in a halal way, use it wisely, and fulfill social responsibilities. The application of the concept of the balance of wealth in the Quran in the economic life of modern Muslims can create an economy that is fair, sustainable, and brings blessings to individuals and society.